PENDAMPINGAN PENERAPAN DIGITAL MARKETING DALAM UPAYA MENGEMBANGKAN UMKM WONG HAYYU CRAFT DI KELURAHAN KAUMAN BLITAR - Muhammad Ahmi Husein; Irfan Wahyu Jatmiko; Ferdy Irwansyah; Zeinnisa Inggit Raytasyah; Ira Wikartika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Blitar City is one of the cities in East Java Province, famous for its outstanding creative economic potential. In theKelurahan in Blitar City, namely Kauman Village, there are micro, small, and medium enterprises (MSMEs) thathave the potential to be developed. In this community service activity, the author partners with MSMEs, which areengaged in the business of producing hand-knitted crafts. In the pandemic conditions two years ago, MSME